Guided and unguided de-escalation from potent P2Y12 inhibitors among patients with acute coronary syndrome: a meta-analysis. Issue 5 (30th August 2021) - Tavenier, Anne H; Mehran, Roxana; Chiarito, Mauro; Cao, Davide; Pivato, Carlo A; Nicolas, Johny; Beerkens, Frans; Nardin, Matteo; Sartori, Samantha; Baber, Usman; Angiolillo, Dominick J; Capodanno, Davide; et al.
Abstract: Aim: Optimal dual antiplatelet therapy (DAPT) in patients undergoing percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS) intends to balance ischemic and bleeding risks. Various DAPT de-escalation strategies, defined as switching from a full-dose potent to a reduced dose or less potent P2Y12 inhibitor, have been evaluated in several ACS-PCI trials. We aimed to compare DAPT de-escalation to standard DAPT with full-dose potent P2Y12 inhibitors in ACS patients who underwent PCI. Methods and results: PubMed, Google Scholar, and Cochrane Central Register of Controlled Trials were searched for eligible randomized controlled trials. Aspirin monotherapy trials were excluded. Five randomized trials ( n  = 10 779 patients) that assigned DAPT de-escalation (genetically guided to clopidogrel n  = 1242; platelet function guided to clopidogrel n  = 1304; unguided to clopidogrel n  = 1672; unguided to lower dose n  = 1170) vs. standard DAPT (control group n  = 5391) were included in this analysis. DAPT de-escalation was associated with a significant reduction in Bleeding Academic Research Consortium ≥2 bleeding (HR 0.57, 95% CI 0.42–0.78; I 2  = 77%) as well as major adverse cardiac events, represented in most trials by the composite of cardiovascular mortality, myocardial infarction, stent thrombosis, and stroke (HR 0.77, 95% CI 0.62–0.96; I 2  = 0%). Notwithstanding the limited power, consistency was noted across various de-escalation strategies. Conclusion: De-escalation of DAPT after PCI for ACS, both unguided and guided by genetic or platelet function testing (PFT), was associated with lower rates of clinically relevant bleeding and ischemic events as compared to standard DAPT with potent P2Y12 inhibitors based on five open-label RCTs reviewed. Graphical Abstract: